2022
DOI: 10.3389/fneur.2022.909403
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to predict futile recanalization of large vessel occlusion before and after endovascular thrombectomy

Abstract: Background and purposeFutile recanalization occurs when the endovascular thrombectomy (EVT) is a technical success but fails to achieve a favorable outcome. This study aimed to use machine learning (ML) algorithms to develop a pre-EVT model and a post-EVT model to predict the risk of futile recanalization and to provide meaningful insights to assess the prognostic factors associated with futile recanalization.MethodsConsecutive acute ischemic stroke patients with large vessel occlusion (LVO) undergoing EVT at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…125 These algorithms are useful to detect LVO, delineate the core, penumbra size and target mismatch, 126 score collaterals, 127 classify stroke mechanisms, 128 and predict outcomes and risk of hemorrhagic transformation after EVT in ischemic stroke patients. 129,130 The role of machine learning is evolving and will continue to play a role in the diagnosis and management of cerebrovascular diseases in the future. Further integration of artificial intelligence and machine learning in acute stroke care is inevitable.…”
Section: Artificial Intelligence and Machine Learning In Acute Ischem...mentioning
confidence: 99%
See 1 more Smart Citation
“…125 These algorithms are useful to detect LVO, delineate the core, penumbra size and target mismatch, 126 score collaterals, 127 classify stroke mechanisms, 128 and predict outcomes and risk of hemorrhagic transformation after EVT in ischemic stroke patients. 129,130 The role of machine learning is evolving and will continue to play a role in the diagnosis and management of cerebrovascular diseases in the future. Further integration of artificial intelligence and machine learning in acute stroke care is inevitable.…”
Section: Artificial Intelligence and Machine Learning In Acute Ischem...mentioning
confidence: 99%
“…Commercially available machine learning algorithms have been integrated into clinical setting to support the time-sensitive decision-making for rapid diagnosis and image analysis; no significant differences have been observed between software [ 125 ]. These algorithms are useful to detect LVO, delineate the core, penumbra size and target mismatch [ 126 ], score collaterals [ 127 ], classify stroke mechanisms [ 128 ], and predict outcomes and risk of hemorrhagic transformation after EVT in ischemic stroke patients [ 129 , 130 ]. The role of machine learning is evolving and will continue to play a role in the diagnosis and management of cerebrovascular diseases in the future.…”
Section: Artificial Intelligence and Machine Learning In Acute Ischem...mentioning
confidence: 99%
“…Recent research has demonstrated the growing application of ML models in the medical sector [11][12][13][14][15][16].ML models incorporate a variety of advanced algorithms to handle different data characteristics, including State-Action-Reward-State-Action , Random Forest Classi er, Deep Q Network, and Support Vector Machine [17].In comparison to traditional regression models, ML has been validated as an effective method for prognosis prediction in modeling due to its capacity to intricately analyze complex non-linear interrelations among variables [18,19], and to enhance prediction accuracy through its superior algorithms, particularly when analyzing large datasets with numerous variables [20,21]. Crucially, the widespread adoption of Electronic Patient Record systems and the extensive use of structured patient data have made sophisticated algorithmic modeling and bedside application feasible [22].…”
Section: Introductionmentioning
confidence: 99%
“…A risk prediction score to mitigate harm among subgroups of patients at risk of FR is warranted. However, minimal studies have explored this area [ 6 ].…”
Section: Introductionmentioning
confidence: 99%